An empirical evaluation of virtual circuit holding time policies in IP-over-ATM networks. - Keshav, S. (IEEE Journal on selected areas in communications)
When carrying Internet protocol (IP) traffic over an asynchronous transfer mode (ATM) network, the ATM adaptation layer must determine how long to hold a virtual circuit opened to carry an IP datagram. We present a formal statement of the problem and carry out a detailed empirical examination of various holding time policies taking into account the issue of network pricing. We offer solutions for two natural pricing models, the first being a likely pricing model of future ATM networks, while the second is based on characteristics of current networks. For each pricing model, we study a variety of simple nonadaptive policies as well as easy to implement policies that adapt to the characteristics of the IP traffic. We simulate our policies on actual network traffic, and find that policies based on least recently used (LRU) perform well, although the best adaptive policies provide a significant improvement over LRU